2018
DOI: 10.1007/s00706-018-2280-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum-binding properties of isosteric ruthenium and osmium anticancer agents elucidated by SEC–ICP–MS

Abstract: Size-exclusion chromatography–inductively coupled plasma–mass spectrometry (SEC–ICP–MS) was used to study the serum-binding preferences of two metallodrugs with anticancer activities in vivo, namely the organoruthenium compound plecstatin-1 and its isosteric osmium analog. The complexes were administered intraperitoneally into mice bearing a CT-26 tumor. Comparing the total metal content of mouse whole blood and serum underlined that the metallodrugs are mainly located in serum and not in the cellular fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…S4, ESI †). This is in agreement with previous crystallographic 72 and molecular modelling studies, 41 which suggested that FFAs with a chain length rC8 are too short to elicit the allosteric switch on albumin. Previous ITC experiments had confirmed that octanoate indeed did not affect the Zn 2+ -binding capacity of BSA.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…S4, ESI †). This is in agreement with previous crystallographic 72 and molecular modelling studies, 41 which suggested that FFAs with a chain length rC8 are too short to elicit the allosteric switch on albumin. Previous ITC experiments had confirmed that octanoate indeed did not affect the Zn 2+ -binding capacity of BSA.…”
Section: Resultssupporting
confidence: 93%
“…67 ICP-MS has also been used to inspect variations in the levels of free metal ions in serum obtained from patients with bipolar disorder undergoing different treatments. 68 Other researchers have employed size exclusion chromatography (SEC) paired with ICP-MS/AES to study metal binding to plasma proteins, [69][70][71][72][73] and the effect of chelating agents on plasma metal speciation. 74,75 In this study, we have also utilised SEC in conjunction with offline ICP-MS analysis to investigate zinc speciation changes in foetal calf serum (FCS) and human blood plasma, upon addition of free fatty acids (FFAs).…”
Section: Introductionmentioning
confidence: 99%
“…24 However, a 2 h treatment revealed a virtually identical organ distribution pattern for plecstatin-1 and its isosteric osmium-analogue, suggesting that the compounds remain largely intact in vivo for this time period. 23 The compounds are probably stabilized by rapid non-covalent binding to serum proteins, 31 which was already observed for the ruthenium(III)-based KP1019. 32 In order to investigate the impact of the hydrolysis behaviour on the target selectivity of plecstatins, time-dependent target profiling experiments were performed using cell lysates of HCT116 colon carcinoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…For a metalloprotein speciation analysis, the most frequently applied was high-performance liquid chromatography (HPLC) hyphenated to inductively coupled plasma mass spectrometry (ICP-MS) detector. Among HPLC techniques, size exclusion chromatography (SEC) in combination with ICP-MS was used for speciation of metalloproteins [28] and in the investigations of serum binding properties of anticancer agents [29]. However, the low resolution of the SEC, which does not always allow selective separation of proteins, and possible irreversible binding of proteins to the column stationary phase, are the major limitations of this technique.…”
Section: Introductionmentioning
confidence: 99%